АBILITY AND SUITABILITY TO BECOME A DRIVER (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
Improving driver training methods, monitoring physical condition, professional selection, improving their professional qualifications, administrative and legal measures applied to violators, as well as financial incentives are important factors that directly affect driver safety.